2021
DOI: 10.1021/acsabm.1c01160
|View full text |Cite
|
Sign up to set email alerts
|

Using Platelet-Rich Plasma Hydrogel to Deliver Mesenchymal Stem Cells into Three-Dimensional PLGA Scaffold for Cartilage Tissue Engineering

Abstract: The synthetic biodegradable polyester-based rigid porous scaffolds and cell-laden hydrogels have been separately employed as therapeutic modality for cartilage repair. However, the synthetic rigid scaffolds alone may be limited due to the inherent lack of bioactivity for cartilage regeneration, while the hydrogels have insufficient mechanical properties that are not ideal for load-bearing cartilage applications. In the present study, a hybrid construct was designed to merge the advantage of 3D-printed rigid po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The usual techniques for preparing modified polyesters for artificial bone-substitute materials involve 3D printing [ 51 , 61 , 65 , 66 , 72 , 74 , 75 , 76 ], thermally induced phase separation (TIPS) [ 32 ], salt leaching [ 32 , 69 , 79 ], solvent casting [ 33 , 35 , 77 , 79 ], electrospinning [ 60 , 64 , 70 ], copolymerization [ 31 ], and polycondensation [ 73 ].…”
Section: Orthopedic Applicationsmentioning
confidence: 99%
“…The usual techniques for preparing modified polyesters for artificial bone-substitute materials involve 3D printing [ 51 , 61 , 65 , 66 , 72 , 74 , 75 , 76 ], thermally induced phase separation (TIPS) [ 32 ], salt leaching [ 32 , 69 , 79 ], solvent casting [ 33 , 35 , 77 , 79 ], electrospinning [ 60 , 64 , 70 ], copolymerization [ 31 ], and polycondensation [ 73 ].…”
Section: Orthopedic Applicationsmentioning
confidence: 99%
“…The clotting ability of activated platelet derivatives expands their application so that they can be applied to the surface of CTE constructures as a coating ( Luo et al, 2020 ), or gel with a 3D printed frame emerging-in as shown in Figure 5A ( Tang Y. et al, 2021 ). In such cases, the platelet derivatives are attached to molded biomaterials, therefore the influences on mechanical and degradation properties are minor.…”
Section: Addition Of Platelet Derivatives In Ctementioning
confidence: 99%
“…(A) 3D printed PLGA frames are immersed in MSC-suspended PRP solution, and then the gelation of PRP is induced by addition of CaCl 2 solution with thrombin to complete the CTE construct. Reproduced with permission from Tang Y. et al (2021) . (B) Biomaterials, MSCs, and PRP are all mixed together before fabrication process to construct the synergistic scaffold.…”
Section: Addition Of Platelet Derivatives In Ctementioning
confidence: 99%
See 1 more Smart Citation
“…43 The lack of standards for PRP in terms of factors such as centrifugation speed and time leads to a wide variation in platelet and leukocyte concentrations, which affects the therapeutic effect. 44 In sum, more and more studies have shown that PRP can improve clinical cartilage pathology, and some scholars have applied PRP to cartilage tissue engineering, [45][46][47][48] but how and why it plays a role in cartilage repair is unclear, 49 which can be used as the next research direction. likely to induce hyaline cartilage production than BMP7, IGF1 or IGF2.…”
Section: Prp Therapymentioning
confidence: 99%